Epidemiological features of irritable bowel syndrome in a Turkish urban society - Celebi, S; Acik, Y; Deveci, SE; Bahcecioglu, IH; Ayar, A; Demir, A; Durukan, P (Wiley, 2004)
Background and AimL Irritable bowel syndrome (IBS) is a widespread functional bowel disorder and its prevalence in Western societies ranges from 3-20%. The present study aimed to determine the prevalence of IBS in eastern Turkey, particularly in urban parts of Elazig where 250 000 people live. Methods: Of the 18 primary care centers, four were randomly selected for this study. All individuals (aged >17 years) living around the service area of these health centers were included. A total of 1900 subjects were randomly selected using the personal health records from the primary care centers. The total number of subjects that could be contacted was 1766. A questionnaire with multiple choice questions was applied to the subjects by medical students using the face-to-face technique. Prevalence of IBS and distribution of symptoms were evaluated by the Rome II criteria. Results: Of the 1766 subjects, 45.4% were male and 54.6% were female. Prevalence of IBS was 5% in males, 7.4% in females and 6.3% overall. The percentage of subjects with IBS in the 17-30 years age group was 26.2%; 52.3% in the 30-50 years age group and 21.6% in the above 50 years age group. Prevalence of IBS was highest (10.2%) in persons who were illiterate and lowest (3.0%) in university graduates. A positive correlation was determined between low economical status and prevalence of IBS (P < 0.05). Conclusions: Although IBS is widely present in Turkey, its prevalence is lower than that reported in Western communities. In the region where this study was carried out, IBS was more prevalent in females and in individuals with low educational and economical status. (C) 2004 Blackwell Publishing Asia Pty Ltd.
Keywords: irritable bowel syndrome; prevalence; Rome II criteria; Turkey